Answer:
<u>Linear relationship</u>: increasing or decreasing one variable will cause a corresponding increase or decrease in the other variable.
<u>Inverse relationship</u>: the value of one variable decreases as the value of the other variable increases.
<u>Exponential relationship</u>: a constant change in the independent variable (x) gives the same proportional change in the dependent variable (y)
<u>Question 5</u>
As the x-value increases (by one unit), the y-value decreases.
Therefore, this is an inverse relationship.
The y-values are calculated by dividing 35 by the x-value.
![\sf y=\dfrac{35}{x}](https://tex.z-dn.net/?f=%5Csf%20y%3D%5Cdfrac%7B35%7D%7Bx%7D)
**I believe there is a typing error in the table and that the y-value of x = 3 should be 11.67**
<u>Question 6</u>
As the x-value increases, the y-value increases. The y-value increases by a factor of 5 for each x-value increase of 1 unit.
Therefore, this is an exponential relationship.
![\sf y=5^x](https://tex.z-dn.net/?f=%5Csf%20y%3D5%5Ex)
Derivitive of cosx=-sinx
dy/dx sinx=cosx
and use chain rue
2cosx=-2sinx
2cos2x=-4sin2x
so
-2sinx-4sin2x id the deritivitve
Answer:
(x -2) (x- 8) (x+7)
Step-by-step explanation:
The equation in the form y = mx + b is y = 0.35x + 36.
<h3>How to represent a linear equation?</h3>
The equation formed from the expression is a linear equation and should be expressed in the slope intercept form.
y = mx + b
where
Therefore,
y = mx + b
where
- x = the number of monthly minutes used
- y = the total monthly of the Next fell plan
using the coordinates, let's find m
(470, 200.5)(590, 242.5)
Hence,
m = 242.5 - 200.5 / 590 - 470
m = 42 / 120
m = 0.35
Therefore,
y = 0.35x + b
200.5 = 0.35(470) + b
200.5 - 164.5 = b
b = 36
Finally, the equation in the form y = mx + b is y = 0.35x + 36.
learn more on linear equation here: brainly.com/question/24223023
#SPJ1
The area of the shaded region will be the area of the rectangle minus the area of the white square inside of it:
((x+10)(2x+5)) - ((x+1)(x+1))
First, FOIL both of the areas separately:
(2x^2 + 5x + 20x + 50) - (x^2 + x + x + 1)
Simplify within the parentheses by adding like terms:
(2x^2 + 25x + 50) - (x^2 + 2x + 1)
Now, subtract one equation from the other:
2x^2 + 25x + 50
-x^2 - 2x - 1
= x^2 + 23x + 49
This will be the equation for the area.